Evaluation of the Effect of Erector Spinae Plane Block in Patients Undergoing Belt Lipectomy Surgery - Altun, Aysun Yildiz; Demirel, Ismail; Bolat, Esef; Altun, Serdar; Ozcan, Sibel; Aksu, Ahmet; Bestas, Azize (Springer, 2020)
Background The interest in and demand for post-bariatric surgery have increased along with the increase in obesity surgery. Belt lipectomy, during which a circular correction is made in the center of the trunk, is the most commonly performed among these surgical techniques. Postoperative pain is an important problem due to the size of the surgical site and stretched closure. In this study, it was aimed to evaluate the intraoperative and postoperative narcotic analgesic consumption, postoperative analgesic requirement, postoperative visual analog scale (VAS) scores, postoperative nausea and vomiting (PONV), and the first mobilization time in patients with and without erector spinae plane block (ESPB). Methods The files of patients who had undergone belt lipectomy between 2016 and 2019 in our hospital were retrospectively reviewed. Patients who received ESPB were called group 1, and those who did not undergo ESPB were called group 2. Their demographic characteristics, intraoperative and postoperative narcotic and non-narcotic analgesic consumption, VAS scores, PONV, and the first mobilization times were recorded. Results The files of a total of 51 patients, including 23 patients in group 1 and 28 patients in group 2, were reviewed. It was determined that intraoperative and postoperative narcotic analgesic consumption (p < 0.005), PONV (p < 0.005), and the first mobilization time (p < 0.005) were significantly lower in group 1 compared with group 2. Conclusion The use of the ESP block in belt lipectomy surgeries significantly reduces intraoperative and postoperative narcotic analgesic consumption and pain scores.
Keywords: Belt lipectomy; Erector spinae plane block; Analgesia